The application of dual-layer remote phosphor geometry in achieving higher color quality of WLEDs - My Hanh Nguyen Thi; Phung Ton That; Hoang Van Ngoc (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
If remote phosphor structures are put into comparison with conformal phosphor or in-cup phosphor, their luminous flux are better, but the color quality is not as elevated. This leads to an obvious need of a practical solution to enhance color quality. Therefore, many studies were carried out to achieve this purpose, and so is ours. We proposed using two layers of phosphor in WLEDs to achieve better rendering ability and chromatic performance. The identical WLEDs with different color temperatures, 5600 K-8500 K, were used and reported in this paper. Our research consists of two parts, which are placing a layer of red phosphor SrwFxByOz:Eu2+,Sm2+on the yellow YAG:Ce3+ phosphor layer at first, and then specifying an appropriate SrwFxByOz:Eu2+,Sm2+ concentration to reach the highest color performance. It is shown that with the contribution of SrwFxByOz:Eu2+,Sm2+,the color rendering index (CRI) and color quality scale (CQS) are increased. This can be explained by the increased amount of red light components in the WLEDs when the concentration of SrwFxByOz:Eu2+,Sm2+ was greater. However, excessive SrwFxByOz:Eu2+,Sm2+ will cause the reduction in the flux, which has been proven by the application of Mie scattering and the Lambert-Beer law. Therefore, the conclusion will present an optimal amount of SrwFxByOz:Eu2+,Sm2+ to obtain high color quality while minimizing the light loss.